HUBUNGAN FAKTOR RISIKO PEMBENTUKAN SEDIMEN URINE PADA SOPIR DI KOTA BENGKULU - Susiwati Susiwati; Jon Farizal; Leni Marlina (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2020)
Urine sediment examination is one of the important routine checks in filter screening. In this examination, it must be mentioned the amount of sediment element per field of view especially for the type of urine crystals and other non-organic elements. The driver is one of the professions that require sitting for a long time with the habit of holding back urine and rarely drinking water. The purpose of this study was to determine whether there is a relationship between long sitting habits, rarely drinking water and often withholding urine from the process of urine sediment formation in bus drivers in the city of Bengkulu. The research method used was a cross-sectional design with a sample of 180 respondents. The morning urine of the respondent was examined microscopically if there were any urine sediments found. Frequency distribution of urine sediment in the bus driver results showed 6 respondents (10%) the number of abnormal erythrocytes, 4 respondents (6.7%) the number of abnormal leukocytes, 5 respondents (8.3%) positive epithelium, all respondents (100%) showed negative cylindrical and parasitic, 3 respondents (5%) were positive for bacteria and 11 respondents (18.3%) were positive for crystals. Whereas the truck driver found 2 respondents (3.3%) the number of abnormal erythrocytes, 3 respondents (5%) the number of abnormal leukocytes, 3 respondents (5%) positive epithelium, all respondents (100%) showed negative cylinders, bacteria and parasites, and 5 respondents (8.3%) positive Crystal. There is a significant difference in the length of sitting between the bus driver and the truck driver.